PENGGUNAAN MODEL PEMBELAJARAN CIRCLE AND QUICK ON THE DRAW UNTUK MENINGKATKAN KEMAMPUAN KERJASAMA SISWA PADA MUATAN PEMBELAJARAN IPAS - Rahmatulhusna; M. Syahrul Rizal; Sumianto; Melvi Lesmana Alim; Syahrial (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study investigates the application of the Circle and Quick on the Draw learning model in IPAS (Science, Social Studies, and Arts) lessons. The primary objective is to enhance students' collaboration skills within this subject this research is a classroom action research conducted in Class V at SD Negeri 010 Ratu Sima Dumai. This model is a group work model that emphasizes speed in activities such as thinking, reading, speaking, writing, and answeringquestions It aims to encourage active learning by having students work together to find, answer, and report information from various sources in agame-likesetting. Student collaboration is crucial as it involves working together to achieve common goals, respecting differing opinions, and fostering mutualsupport. It helps students develop social skills, manage conflicts constructively, and prepare for future professional life. ndicators of collaboration include communication, contribution within the group, respecting individual differences, encouraging participation, and completing tasks on time. Based on pre-action data, the collaboration skills of students in Class V at SD Negeri 010 Ratu Sima Dumai were low, with only 33.33% of students achieving the mastery criterion. Following the implementation of the Circle and Quick on the Draw model through two action cycles, a significant improvement in student collaboration skills was observed. In Cycle I, Meeting I, the percentage of students who achieved mastery in collaboration was 37.5%, increasing to 37.5% in Cycle I, Meeting II, 66.67% in Cycle II, Meeting I, and reaching 83.33% in Cycle II, Meeting II. This improvement indicates that the Circle and Quick on the Draw learning model is effective in enhancing student collaboration skills, successfully meeting the classical mastery target of 80%. concludes that the use of the Circle and Quick on the Draw learning model effectively improved student collaboration skills in IPAS lessons in Class V at SD Negeri 010 Ratu Sima Dumai.